1987
DOI: 10.1111/j.1365-201x.1987.tb10621.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute haemorrhagic hypotension during pregnancy and lactation in conscious goats

Abstract: Effects of acute, short-lasting haemorrhage have been studied in six goats. The experiments were made 55 +/- 3 days (mid-pregnancy = MP), and 24 +/- 2 days (late pregnancy = LP) before parturition, in lactation weeks 3-8, and in the non-pregnant, non-lactating (= control) period. The room temperature was kept at 20 +/- 1 degrees C, except during one experimental series in lactating goats, which was performed at +30 degrees C. Approximately the same volume of blood had been removed in all periods, when the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The last-mentioned result is somewhat surprising since labour involves intense muscular work, and exercise can induce the release of vasopressin in a dose-related fashion in humans (Wade 1984). High vasopressin levels during labour could also be explained by increased plasma osmolality (Landgraf et al 1983) and haemorrhage (Larsson et al 1978, Olsson et al 1987. The increases in vasopressin during expulsion in both goats and heifers may therefore be secondary to several causes.…”
Section: Figurementioning
confidence: 99%
“…The last-mentioned result is somewhat surprising since labour involves intense muscular work, and exercise can induce the release of vasopressin in a dose-related fashion in humans (Wade 1984). High vasopressin levels during labour could also be explained by increased plasma osmolality (Landgraf et al 1983) and haemorrhage (Larsson et al 1978, Olsson et al 1987. The increases in vasopressin during expulsion in both goats and heifers may therefore be secondary to several causes.…”
Section: Figurementioning
confidence: 99%
“…This change was first noted by Humphreys and Joels (97,98) in an extensive series of studies in anesthetized pregnant rabbits, in which reductions in carotid sinus pressure failed to elicit normal increases in arterial pressure and peripheral vascular resistance. Since then, arterial baroreflex impairment has been documented in several species studied in the conscious state, including dogs (23), rats (24,124), rabbits (21,97,162), goats (152), sheep (104,123), and humans (16,79,122,164,175,193). Reflex responses to atrial stretch are also blunted (51,94,95,103), which may contribute to retention of the expanded blood volume.…”
mentioning
confidence: 99%
“…Pregnant women are prone to orthostatic hypotension, due to blunted reflex activation of the sympathetic nervous system and inadequate peripheral vasoconstriction (56,122,132). Moreover, in many species, pregnancy interferes with the normal ability to maintain arterial pressure during hemorrhage (26,36,99,152,186). Hemodynamic studies have revealed that in pregnant animals, arterial pressure falls with less blood loss due to both a failure to maintain cardiac output and also inadequate peripheral vasoconstriction (22,36).…”
mentioning
confidence: 99%
“…Several studies have documented that pregnant animals are less able to maintain arterial pressure during haemorrhage (Humphreys & Joels 1985;Tabsh et al 1986;Olsson et al 1987;Brooks & Keil 1994a). This change in cardiovascular homeostasis is highlighted in Fig.…”
Section: Pregnancy Alters Haemodynamic Responses To Haemorrhagementioning
confidence: 93%
“…1, bottom), it appears that with a roughly equivalent absolute volume loss, the pregnant animals still experienced greater hypotension, ruling out this argument. An inability to regulate arterial pressure during haemorrhage has also been described in other species including goats, sheep and rabbits (Humphreys & Joels 1985;Tabsh et al 1986;Olsson et al 1987). Moreover, pregnant women are known to be more susceptible to orthostatic hypotension (Metcalfe et al 1986).…”
Section: Pregnancy Alters Haemodynamic Responses To Haemorrhagementioning
confidence: 97%